The Challenges of Pancasila Socio-Democracy in The Era of Networked Society: Liberal Democracy and Religious Fundamentalism - Toto Sugiarto; Naupal Asnawi (El Madani : Jurnal Dakwah dan Komunikasi Islam, 2023)
Socio-democracy, along with this writing style, is in the heart of the nation of Indonesia which is the key essence of Pancasila. The fundamental philosophical values of Indonesia’s socio-democracy is a typical democracy of the Indonesian nation. This socio-democracy is part of the Pancasila ideology. The socio-democracy, in Pancasila, was introduced by Sukarno, the first president of Indonesia to face and respond to two major challenges, market fundamentalism, and religious fundamentalism. Market fundamentalism values increased individual satisfaction at the expense of society and public service, and put monetary reward as the only measurement. The socio-democracy wants to go against this while paving the way for shared values and shared prosperity. Religious fundamentalism refers to a closed and exclusive religious interpretation and practice of faith which alienates common and shared life and wants to force all people to be under this practice. The socio-democracy wants to build a platform for all to be happy and shares public life, and this avoids the trap of religious fundamentalism. In looking into the concept and practice of socio-democracy, this study uses qualitative methods and literature. Various reading materials related to this topic were reviewed and then became material for research analysis. Sukarno's thoughts on socio-democracy and Manuel Castells on network society are two examples of thoughts. Those provide the key frame of this paper. The purpose of this article is to describe the two big challenges faced by this nation, i.e., liberal democracy and religious fundamentalism. This article assesses or even anticipates whether those two big challenges tear the nation apart going into the next decades.